Analisis Perspektif Pelanggan terhadap Kepuasan Kinerja Pelayanan Rumah Sakit Belleza Kedaton Bandar Lampung - Sari, Ratna Dewi Puspita; Wulansari, Rifda; Muchtiar, Mulyadi; Budiman, Dicky; Adjie, JM Seno; Muslikh, Muslikh; Novita, Dian (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Belleza Kedaton Hospital Bandar Lampung faces challenges in ensuring the quality of health services in the midst of its transformation into a general hospital and the implementation of a partnership with BPJS Health since 2024. This study aims to examine the relationship between service quality dimensions (Tangibles, reliability, responsiveness, assurance, and empathy) with patient satisfaction, and its impact on hospital operational performance. This study uses quantitative with a Cross Sectional approach. The sample was 100 general patient respondents and 100 BPJS patients, with a Stratified Random Sampling technique. Data were collected through SERVQUAL (Service Quality) questionnaire and numeric scale for satisfaction and analyzed using Univariate. The results showed the gap score of attributes - attributes of statements based on the SERVQUAL dimension in patients before BPJS in 2023 the highest gap score was at attribute statement number 27 “The nurse informs and explains the actions to be taken” of 1.75. While the lowest gap score is on statement attribute number 41 “Ease and speed of the administrative process” of 0.06. In 2024, the highest gap score is on statement attribute number 31 “Patient administration procedures are easy and straightforward” by 2.17. While the lowest gap score is on statement attribute number 41 “The appearance of health workers and personnel (doctors, nurses) is clean and neat” by 0.17. Based on the results of the study, it can be seen that the analysis of customer perspectives based on the emphaty dimension decreased satisfaction in 2023 respondents who stated that they were satisfied by 71 people (71.0%) and decreased in 2024 to 47 people (47.0%), the Tangible dimension found a decrease in satisfaction in 2023 respondents who stated they were satisfied by 65.0% and decreased in 2024 to 49.0%, the reliability dimension of service performance satisfaction decreased satisfaction in 2023 respondents who stated they were satisfied by 77. 0% and decreased in 2024 to 46.0%, the assurance dimension of service performance satisfaction decreased satisfaction in 2023 respondents who expressed satisfaction of 74.0% and decreased in 2024 to 42.0%, the responsiveness dimension of service performance satisfaction decreased satisfaction in 2023 respondents who expressed satisfaction of 70.0% and decreased in 2024 to 40.0%. Based on the analysis of service performance satisfaction, it can be seen that there was a decrease in satisfaction in 2023 respondents who stated that they were very satisfied by 46.0% and decreased in 2024 to 14.0%.  Keywords: Customer Perspective, Satisfaction, Service PerformanceABSTRAK Rumah Sakit Belleza Kedaton Bandar Lampung menghadapi tantangan dalam memastikan mutu pelayanan kesehatan di tengah transformasi menjadi rumah sakit umum dan penerapan kemitraan dengan BPJS Kesehatan sejak 2024. Penelitian ini bertujuan untuk mengkaji hubungan antara dimensi mutu pelayanan (Tangibles, reliability, responsiveness, assurance, dan empathy) dengan kepuasan pasien, serta dampaknya terhadap kinerja operasional rumah sakit. Penelitian ini menggunakan kuantitatif dengan pendekatan Cross Sectional. Sampel yaitu sebanyak 100 responden pasien umum dan 100 orang pasien BPJS, dengan teknik sampel Stratified Random Sampling. Data dikumpulkan melalui kuesioner SERVQUAL (Service Quality) dan skala numeric scale untuk kepuasan dan dianalisis menggunakan Univariat. Hasil penelitian menunjukkan gap skor atribut – atribut pernyataan berdasarkan dimensi SERVQUAL pada pasien sebelum BPJS tahun 2023 gap skor yang paling tinggi ada pada atribut pernyataan nomor 27 “Perawat menginformasikan dan menjelaskan tindakan yang akan dilakukan” sebesar 1,75. Sedangkan gap skor yang paling rendah ada pada atribut pernyataan nomor 41 “Kemudahan dan kecepatan proses administrasi” sebesar 0,06. Tahun 2024 gap skor yang paling tinggi ada pada atribut pernyataan nomor 31 “Prosedur administrasi pasien mudah dan tidak berbelit-belit” sebesar 2,17. Sedangkan gap skor yang paling rendah ada pada atribut pernyataan nomor 41 “Penampilan petugas dan tenaga kesehatan (dokter, perawat) bersih dan rapi” sebesar 0,17. Berdasarkan hasil penelitian dapat diketahui analisis perspektif pelanggan berdasarkan dimensi emphaty terjadi penurunan kepuasantahun 2023 responden yang menyatakan puas sebesar 71 orang (71,0%) dan menurun di tahun 2024 menjadi sebesar 47 orang (47,0%), dimensi Tangible didapati terjadi penurunan kepuasan tahun 2023 responden yang menyatakan puas sebesar 65,0% dan menurun di tahun 2024 menjadi sebesar 49,0%, dimensi reliability terhadap kepuasan kinerja pelayanan terjadi penurunan kepuasan tahun 2023 responden yang menyatakan puas sebesar 77.0% dan menurun di tahun 2024 menjadi 46,0%, dimensi assurance terhadap kepuasan kinerja pelayanan terjadi penurunan kepuasan tahun 2023 responden yang menyatakan puas 74.0% dan menurun di tahun 2024 menjadi sebesar 42,0%, dimensi responsiveness terhadap kepuasan kinerja pelayanan terjadi penurunan kepuasan tahun 2023 responden yang menyatakan puas sebesar 70.0% dan menurun di tahun 2024 menjadi sebesar 40,0%. Berdasarkan analisis kepuasan kinerja pelayanan dapat diketahui bahwa terjadi penurunan kepuasan tahun 2023 responden yang menyatakan puas sekali sebesar 46,0% dan menurun di tahun 2024 menjadi sebesar 14,0%.  Kata Kunci: Perspektif pelanggan, kepuasan, kinerja pelayanan